Cytogenetic disorders in Triticum aestivum L. cells affected by radionu-clide contamination of water reservoirs in the alienation zone of Chornobyl NPP - Yakymchuk, R.A. (Вiopolymers and Cell, 2018)
Aim. To study frequency and spectrum of chromosome aberrations in the cells of Triticum aestivum L. root meristem under a prolonged effect of radionuclide contamination of water reser-voirs in the near alienation zone of Chornobyl NPP (ChNPP). Methods. The seeds of two soft winter wheat varieties were treated with samples from water reservoirs in the alienation zone of Chornobyl NPP. Anatelophase analysis of chromosome aberrations in crushed cytological prepa-rations of apical meristem of primary rootlets was used. Results. Radionuclide contamination of water reservoirs in the near alienation zone of Chornobyl NPP causes an increase in the aberrant cell frequency and mitosis disorders by 1.6-4.2 times. The highest level of cytogenetic activity is typical for radionuclide contamination of reservoir-cooler of ChNPP, Semyhodskyi backwater, drainage-way № 3 of ChNPP and Lake Hlyboke. Their spectrum type is mostly represented by single and paired acentric fragments, bridges and lagging chromosomes. Conclusion. A prolonged effect of ionizing radiation of radionuclide contaminations of water reservoirs of the near alien-ation zone of ChNPP is characterized by a high cytogenetic activity. The correlation between the chromosome aberration level and the scope of specific radionuclide activity of water reservoirs was not found, which may prove the induction of cytogenetic disorders under the radiation effect in the low-rate range. The increased level of aneuploid cells and those with multiple chromosome aberrations confirms a genetic danger for the organisms in water reservoirs even with a low spe-cific activity of radionuclide contamination. Мета. Вивчити частоту та спектр хромосомних аберацій в клітинах кореневої меристеми Triticum aestivum L. за пролонгованої дії радіонуклідних забруднень водойм ближньої зони відчуження Чорнобильської АЕС. Методи. Спосіб впливу водними розчинами мутагенів на насіння і проростки. Ана-телофазний метод аналізу хромосомних аберацій на давлених цитологічних препаратах апікальної меристеми первинних корінців. Результати. Радіонуклі-дне забруднення водойм ближньої зони відчуження ЧАЕС викликає зростання в 1,6-4,2 рази частоти аберантних клітин та порушень мітозу. Найвищий рівень цитогенетичної активності характерний для радіонуклідного забруд-нення водойми-охолоджувача ЧАЕС, Семиходського затону, відвідного каналу № 3 ЧАЕС та оз. Глибоке. Спектр їх типів переважно представлений одиничними і парними ацентричними фрагментами, мостами й відстаючими хромосомами. Висновки. Пролонгована дія іонізуючих випромінювань радіонуклідних забруднень водойм ближ-ньої зони відчуження ЧАЕС характеризується високою цитогенетичною активністю. Залежності між рівнем хро-мосомних аберацій та величиною питомої активності радіонуклідів водойм не виявлено, що може свідчити про індукування цитогенетичних порушень за дії опромінення в діапазоні низьких доз. Підвищений рівень анеуплоїд-них клітин та клітин з множинними хромосомними абераціями свідчить про генетичну небезпеку для організмів навіть водойм з низькою питомою активністю радіонуклідного забруднення. Цель. Изучить частоту и спектр хромосомных аберраций в клетках корневой меристемы Triticum aestivum L. при пролонгированном действии радионуклидных загрязнений водоемов ближней зоны отчуждения Чернобыльской АЭС. Методы. Способ влияния водными растворами мутагенов на семена и проростки. Ана-телофазный метод анализа хромосомных аберраций на давленных цитологических препаратах апикальной меристемы первичных корешков. Результаты. Радионуклидное загрязнение водоемов ближней зоны отчуждения ЧАЭС вызывает возрас-тание в 1,6-4,2 раза частоты аберрантных клеток и нарушений митоза. Самый высокий уровень цитогенетической активности характерный для радионуклидного загрязнения водоема-охладителя ЧАЭС, Семиходской заводи, от-водящего канала № 3 ЧАЭС и оз. Глубокое. Спектр их типов преимущественно представлен единичными и пар-ными ацентрическими фрагментами, мостами и отстающими хромосомами. Выводы. Пролон-ги-ро-ван-ное дейст-вие ионизирующих излучений радионуклидных загрязнений водоемов ближней зоны отчуждения ЧАЭС характе-ризуется высокой цитогенетической активностью. Зависимости между уровнем хромосомных аберраций и значе-нием удельной активности радионуклидов водоемов не выявлено, что может свидетельствовать о индуцировании цитогенетических нарушений при действии облучения в диапазоне низких доз. Повышенный уровень анеуплоид-ных клеток и клеток с множественными хромосомными аберрациями свидетельствует о генетической опасности для организмов даже водоемов с низкой удельной активностью радионуклидного загрязнения.